Effects of temperature and salinity on the reproductive phases of Macrocystis pyrifera (L.) C. Agardh (Phaeophyceae) in the Magellan region - Pablo Rodriguez, Juan; Terrados, J.; Rosenfeld, S.; Mendez, F.; Ojeda Villarroel, Jaime Andrés; Mansilla Muñoz, Andres Omar (My University, 2019)
The region of Magallanes has the world's largest sub-Antarctic environments, including the heterogeneous habitats of archipelagos, fjords, channels, and inlets formed by ice advancing and retreating during Quaternary glacial processes. In marine ecosystems, the temperature, salinity, and photoperiod are key parameters which delimit the survival, reproduction and development of the macroalgae and, therefore, the biogeography of numerous sub-Antarctic species. In this research, we compare the reproductive development patterns in spores of Macrocystis pyrifera coming from places with different salinities along longitudinal and latitudinal gradients in Skyring Sound, Otway Sound, the Strait of Magellan (Possession Bay and Puerto del Hambre), and the Beagle Channel (Paula Bay). Laboratory analyses included four salinities and two different temperatures, comparing the percentage of spore germination, sex ratio in females and male gametophytes, and the development of gametogenesis through the proportion of gametophytes and sporophytes, with a factorial experimental design. The best germination percentages were obtained in Puerto del Hambre; the best sex ratio, on the other hand, was in Skyring Sound; finaly, for gametogenesis development, the best results were obtained in Otway Sound and Possession Bay. We prove the temperature and salinity effect over the studied population; moreover, these results demonstrate that at the end of the cycle each population develops more effectively in their local conditions, evidence of a local adaptation in M. pyrifera populations living in contrasting sites in the same region. This is crucial to understand how these populations react to the effect of environmental stressors; furthermore, the selection of appropriate conditions is also an important factor for the future commercial cultivation management of these important macroalgae.
Keywords: phaeophyta; environmental heterogeneity; salinity; temperature; sub-antarctic region; chile